IDENTITAS ARSITEKTUR MANDAR PADA BANGUNAN DI KELURAHAN BANGGAE KABUPATEN MAJENE - Nurmiati Zamad (Teknosains, 2017)
The results of this study indicate that the typical roof shape ornament Mandar in terms of physical form of the use of roof teppang (Butung-Butung) most are still used with value (± 52%). Ornaments are very significant symbolic meaning why the identity architecture still used on building Mandar ethnic year 1960-2016, especially in buildings Mandar contemporary architecture, and in terms of nonphysical factors are influenced by social status and environmental factors.